ASSESSMENT OF RISK MANAGEMENT OF KAZAKHSTAN BANKS IN CONDITIONS OF GROWTH UNCERTAINTY - Kodasheva G.S,; Shaykhanova G.S,; Zhunusova A.Zh, (Academic Journal of Physical and Chemical Sciences, 2019)
Today, one of the most topical issues is the unstable position of second-tier banks of the Republic of Kazakhstan. The authors found out the cause of the unstable position of the banking system in the country and made a number of proposals for their implementation. If previously it was thought that the inefficiency of the functioning of this system is due to the deterioration of asset quality, risks of implementing aggressive growth strategies or the state of the economy, however, the study showed that banks sit on huge liquidity reserves, investing them on monetary and stock markets, preferring them lending market. That is, for the effective functioning of banks, it is necessary to improve the system of bank management, and to minimize negative impacts, strengthen the risk management process taking into account the factors of uncertainty events.